2019
DOI: 10.1038/s41579-019-0205-6
|View full text |Cite
|
Sign up to set email alerts
|

Origin of viruses: primordial replicators recruiting capsids from hosts

Abstract: Viruses are ubiquitous parasites of cellular life and the most abundant biological entities on earth. It is widely accepted that viruses are polyphyletic but a consensus scenario for their ultimate origin(s) is still lacking. Traditionally, three different scenarios have been considered for the origin of viruses: descent from primordial, pre-cellular genetic elements, reductive evolution from cellular ancestors, and escape of genes from cellular hosts achieving partial replicative autonomy and becoming parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 135 publications
2
171
0
9
Order By: Relevance
“…[3] On December 31, 2019, the Wuhan Municipal Health Committee reported 27 cases of pneumonia with an unknown cause, and many cases were traced to the Wuhan Southern China Seafood Market, which was subsequently closed on January 1, 2020. [4] On January 7, 2020, laboratory tests showed that the pathogen causing the previously unexplained pneumonia was a new type of coronavirus; this pneumonia was then officially named COVID-19 by the World Health Organization. [5,6] The COVID-19 outbreak started in Wuhan and spread rapidly to other provinces and countries.…”
Section: Introductionmentioning
confidence: 99%
“…[3] On December 31, 2019, the Wuhan Municipal Health Committee reported 27 cases of pneumonia with an unknown cause, and many cases were traced to the Wuhan Southern China Seafood Market, which was subsequently closed on January 1, 2020. [4] On January 7, 2020, laboratory tests showed that the pathogen causing the previously unexplained pneumonia was a new type of coronavirus; this pneumonia was then officially named COVID-19 by the World Health Organization. [5,6] The COVID-19 outbreak started in Wuhan and spread rapidly to other provinces and countries.…”
Section: Introductionmentioning
confidence: 99%
“…The ancient origin of picornavirus RNA-dependent RNA polymerase suggests that viral RNA recombination has been a characteristic feature of viruses for billions of years (1, 3, 4). Thus, both asexual and sexual RNA replication mechanisms likely arose coordinately in ancient times.…”
Section: Discussionmentioning
confidence: 99%
“…RNA viruses arose billions of years ago, becoming ubiquitous parasites of cellular life (1). The RNA-dependent RNA polymerase of RNA viruses is monophyletic, providing a means to consider the evolutionary history of all RNA viruses, to compare distinct groups of RNA viruses, and to classify RNA viruses (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, viral genomes are extremely diverse in size, ranging from several thousand to a few million bases, and in genomic content, encode various non-overlapping sets of genes. In fact, there are no genes universally present among all viruses, indicating that a monophyletic explanation of viral origin is implausible 5,6 . Secondly, most viral genes show little to no homology to cellular genes.…”
Section: Introductionmentioning
confidence: 99%